(3eYQaI bGfhf GdJChjd aj ahGFO GdJfRjds - (3eMeO Hf YHO Gddg Hf eMeO GdeYGaQj GdETHjdj GdeGdcj, GdbGVj CHh HcQ GHf GdYQHqj , J (B543 (3g` s
(3ChdgG (B:s
(3CeG HYO CjgG GdCN aEfc SCdJfi Cf CajOc HLed YQHjI hYdhe LdjdI ef cJGH Gddg GdYRjR hCf CJhSW ajg s
(3BNQgG (B:s
(3fgGjJg ai CKfGA JaSjQ bhdg JYGdi (B: (3bGd Ef Gddg GUWaGg Ydjce hRGOg HSWI ai GdYde hGdLSe (B:" (3hYdjg LGA bhdg (B: (3hGdSeGA HfjfGgG HCjO hEfG dehSYhf (B" s
(3GdSaQ GdChds
(3hajg ef GdCMRGH (B: (3Bdes
(3CaJWeYhfs
(3Sjbhd s
(3hGPcQhG Gddg fSNI fajSI YJjbI s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs